Claimed and Controlled Space. The Identificability of Political Spaces in Palestine on the Basis of Written and Archeological Evidence in the Iron Age Kingdom of Moab - Vieweger, Dieter (Archäologischer Anzeiger, 2014)
The Moabite rebellion against Israel in the 9th century BC is variously presented in the written sources. A chronological background can help make the prehistory and the course of the conflict comprehensible. Aspects of religious history surrounding these military campaigns are no less interesting. In view of the ongoing debate about the identifiability of political spaces using archaeological means, the article points out the distinct limitations in archaeology’s ability to make such identifications in a small geographical area or a short historical period.